Preserving and sustaining culture: Traditional clothing in the UNESCO world cultural heritage site Kandy in Sri Lanka - PRIYANKAVIRAJINI MEDAGEDARA KARUNARATNE; G. M. RANATHUNGA; S. S. V. DE SILVA (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research aims to establish that clothing is a material cultural object with intangible heritage value because it signifies and expresses nuanced cultural values and social relationships.Method: The study employed the ethnographic approach to research. Ethnography is the practice of using art and science to describe people and their customs. Descriptive labels were coded into the data. Codes were assigned to each activity, event, and thuppottiya-wearing technique to facilitate comparison and pattern identification. Data reliability and validity were both increased by double-checking with other published literature.Findings: Two distinct kinds of thuppottiya have been identified. KariyaKorala was the name of the thuppottiya used by Diyawadana Nilame, the lay guardian of the Tooth Relic and the head of the service to the relic. While the dresses were nearly identical, there were noticeable differences in the colour, fabric, embellishments, and means they accessorized.Implications/Novel Contribution: Consumers and tourists who value collecting symbolic items have given the Thuppottiya new prominence because it is at the centre of ethnic identity. The author concludes by discussing the difficulties heritage regimes encounter in today’s cultural contexts and proposing solutions for the long-term security of the diverse cultural assets under their care.